Plant invasion in undisturbed ecosystems: the triggering atrributes approach - Gurvich, Diego Ezequiel (2005)
The invasion of a target community by a non-indigenous plant species includes the stages of arrival, establishment and spread, which tend to depend on different characteristics of the invasive species and its context. While the mechanisms behind the invasion of highly disturbed ecosystems are well known, our understanding of the invasion process in undisturbed or weakly disturbed ecosystems is much more limited. Here we propose that, once a non-indigenous species has arrived to a new ecosystem and become established, the likelihood that it spreads, and thus becomes invasive, may depend on just one or very few characteristics, called‘triggering attributes’(TA). We propose that a TA is a vegetative or regenerative attribute discontinuously distributed in comparison to the resident community. This attribute allows the species to benefit from a resource that is permanently or temporarily unused by the resident community. We present an original study case and examples from the literature to illustrate our approach, and we also propose some ways to test it in different ecosystems.